2006
DOI: 10.1157/13086714
|View full text |Cite
|
Sign up to set email alerts
|

Depresión posparto en una ciudad colombiana. Factores de riesgo

Abstract: Postnatal depression is little recognized during the puerperium. It is a major public health problem in Bucaramanga, where an appropriate prenatal monitoring program could reduce it. A follow-up program for mother and child would help its early diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Likewise, according to WHO figures, only 63% of pregnant women in Africa, 65% in Asia, and 73% in Latin America attend at least one prenatal consultation 21 . Other studies have reported a prevalence of 69% 22 and 38.8% 23 , with a median of four consultations per pregnant woman 24 . In 2014, on average, only 52% of pregnant women in developing regions received the recommended number of prenatal visits during pregnancy 25 .…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, according to WHO figures, only 63% of pregnant women in Africa, 65% in Asia, and 73% in Latin America attend at least one prenatal consultation 21 . Other studies have reported a prevalence of 69% 22 and 38.8% 23 , with a median of four consultations per pregnant woman 24 . In 2014, on average, only 52% of pregnant women in developing regions received the recommended number of prenatal visits during pregnancy 25 .…”
Section: Discussionmentioning
confidence: 91%
“…Encontramos diferencias en mujeres urbanas y rurales. Estos resultados confirman los encontrados en otros estudios donde la DP se relaciona con el lugar de procedencia (25)(26)(27)(28)(29). En Colombia, se ha demostrado que los factores psicosociales juegan un rol preponderante en el desencadenamiento de la DP (32).…”
Section: Discussionunclassified
“…Este inusual hallazgo coincide también en patologías como estrés, ansiedad y trastornos de humor los cuales son más frecuentes en estratos sociales altos (33,34). También se afirma que la tasa de depresión aumenta entre 10 y 15 % en población con características vulnerables como la pobreza, la criminalidad y las carencias generales (24)(25)(26)(27)(28)(29)(30). Por otro lado, se podría especular que en la etapa perinatal, las mujeres con mejor nivel socioeconómico y mayor acceso educativo, conciben la depresión posparto como "algo normal", esto es, como un estado por el que toda mujer tiene que pasar durante y después del embarazo y, por lo tanto, no es cuestionable, preocupante y mucho menos atendida; esto, en términos de salud es delicado, puesto que esta percepción de "normalidad" lleva a no tener que preocuparse por las consecuencias sociales y de salud que puedan causar dicha condición clínica y, mucho menos, a proponer opciones preventivas.…”
Section: Discussionunclassified
“…Having two sources of income (partner and family) was found to be a protective factor. Anxiety was associated with the presence of depression, psychological violence, and lack of confidence in the partner [19,20]. Research by Loaiza and Sánchez, 2019, at the Versalles Clinic in the department of Caldas found that the prevalence of PPD in the evaluated population was 26%.…”
Section: Epidemiology and Risk Factors Of Ppdmentioning
confidence: 93%